The epistemic validity of religious propositions: An analysis based on Suhrawardi’s logic - Javdaniyan, Saeed (Sofia, 2026)
This article examines the logical admissibility of religious propositions through the framework of Suhrawardi’s logic. It does not seek to confirm or refute religious claims, but to assess whether such propositions satisfy the minimal conditions required for epistemic evaluation. Four criteria derived from Suhrawardi’s logic structure the analysis: definability of the subject, self-evidence as the starting point of cognition, the capacity to generate genuine knowledge, and the preservation of the distinction between existence and essence. The study suggests that many widely employed religious propositions encounter significant difficulties in meeting these logical requirements. They often lack clearly determinate conceptual content, may not provide a legitimate epistemic starting point, and do not readily culminate in analyzable knowledge. Moreover, by loosening or suspending the relation between essence and existence, they tend to resist rational assessment. Consequently, within this strictly logical framework, such propositions can be understood as tending to remain outside, or at best at the margins of, epistemic validity.